Análisis de la evaluación histopatológica testicular del efecto de la castración química con tintura de yodo vs ácido láctico en la producción cuyera andina en la provincia de Imbabura - Loza Cuesta, Nicole Alejandra (2018)
The objective of this study was to evaluate the post-castration chemical effect, lactic acid vs. Iodine tincture as sclerosing chemicals in the testis of the guinea pigs by histopathological analysis, in order to induce a testicular fibrosis. Sixteen whole guinea pigs were randomly selected, which were divided into three groups of five individuals; nevertheless, one more animal was included to be able to analyze its anatomical structure macroscopically. The testicle was also analyzed microscopically to be able to guide the diagnosis. This animal belonged to the control group. The control group had six animals, to which no method of castration was applied. Experimental group N 1 had 5 animals. They were applied 2 percent iodine tincture. On the other hand, experimental group N 2 had 5 animals and lactic acid was applied. Once chemically castrated, they were sacrificed properly, respecting animal welfare. An appropriate necropsy was performed and the testicles were sent to the laboratory to be analyzed. The histopathological study was performed at 7, 14, 21, 28, 35 and 42 days and the sacrifice of one animal per group was carried out. It was concluded that the tincture of iodine came to fibrosis in a grade IV, hyalinizing seminiferous tubules, decreasing germ cells and destroying the parenchyma of the testicle in the first week after castration without affecting its feed conversion index since animals castrated with tincture of iodine gained more weight.